The Use of Mind Mapping Technique to Increase EFL Students’ Motivation in Writing (A Case Study at the Eighth Grade of A Junior High School in Brebes) - Leni Sapitri; Etika Rachmawati; A M Surachmat (Universitas Bengkulu, 2019)
This article focuses on describing the implementation of mind mapping technique to increase students’ motivation in writing descriptive text. An English teacher and 36 students in a Junior high school in Brebes participated in this study. A qualitative design was used, and data were collected through classroom observation, questionnaire and interview. This study found that the teacher did three steps in implementing mind mapping: giving students image of mind mapping, designing the writing task, and asking students to finish the writing task. Meanwhile, interview data indicated that most students enjoyed learning descriptive text by means of mind mapping. Regarding students’ motivation, data from observation revealed that most students enjoyed the activities, as seen from their enthusiasm. Likewise, questionnaire data indicated that most students gave positive perceptions towards the use of mind mapping. Most of them strongly agree with the statement that this strategy can make the learning process become imaginative. In short, it can be concluded that the teacher has successfully applied mind mapping technique. It can make the students enjoy and more interested in learning descriptive text. Therefore, the writers suggest that teachers apply various strategies in teaching and learning process, especially mind mapping, to create an enjoyable classroom atmosphere. Meanwhile, other researchers are recommended to discover the use of mind mapping in teaching other text types